ANALISIS NILAI PENDIDIKAN MORAL PADA BUKU TEMATIK TERHADAP PERKEMBANGAN KARAKTER SISWA SD NEGERI 101744 DESA KLAMBIR - Dinda Syahfitri; Nuri Ramadhan; Layil Safitri (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2023)
The form of this research is qualitative research. The research method used is descriptive qualitative. The data of this study are the values of Moral Education and Student Character Development in the 2013 curriculum thematic books. The data sources used in this study are thematic books with themes 1 (one) and 2 (two). Data collection techniques with interviews and documentation. The results of this study reveal several things from the thematic learning book where the values of moral education and character development in the thematic learning book produce 42 data, with 2 data divisions, and 3 sub themes on themes 1 and 2. In theme 1 there are 21 data with division 3 sub themes, and in theme 2 there are 21 data divided into 3 sub themes. The research subjects were teachers of SD Negeri 101744 Klambir Village, totaling 3 (three) teachers. With the results of teacher interviews, namely: 1) In thematic learning there is moral education and character development and concepts in the material so that the knowledge acquired by students can be implemented in the form of practice outside of school. 2) The teaching materials used are expected to be in accordance with the KD and the indicators developed are also in accordance with the curriculum used. 3) The learning process is not just giving a description of the material, but educators must also deliver material simultaneously to strengthen knowledge about material related to moral education and the development of students' character.